Strategic Policies of Local Government to Control Illegal Fishing in Waters Area of Morotai Island Regency - Muhlis Hafel; Lisda Ariani Simabur (AIBPM Publisher, 2020)
This study aims to determine the policies implemented by Morotai Island Regency Government to anticipate illegal fishing by fishermen from Philippines, Thailand, Taiwan, China and other countries in the sea territorial of the island of Morotai. This study used the qualitative approach based on a case study in Morotai Island Regency. The results of this study indicate that the local government of Morotai established two strategic policies to control illegal fishing activities, including proposing Morotai Island as a Special Economic Zone (ZEK), and developing a Community-based surveillance system (Siswamas). These two are expected to be able to fight off illegal fishing.